PELAKSANAAN ELECTRONIC GOVERNMENT MELALUI APLIKASI LEMBAGA PERKREDITAN DESA KELAN MOBILE PADA LEMBAGA PERKREDITAN DESA ADAT KELAN KABUPATEN BADUNG - Kurnia Dewi, Putu Shinta; Supriliyani, Ni Wayan; Winaya, I Ketut (CITIZEN CHARTER, 2024)
Electronic Government is a government governance system based on digitalization supported by information and communication technology. One form of E-Governemnt is through the Kelan Mobile Village Credit Institution application. The Kelan Mobile Village Credit Institution application is a digitalization baes financial service transaction application in order to be able to provide convenient service only via smartphone, so that services provided by village Credit Institutions can be carried out anywhere without having to perform conventional services which take up more time. the application of the Kelan Mobile Village Credit Institution as an embodiment of the EGovernment concept still has several obstacles, namely that socialization has not been optimal, community adaptation from conventional to digital is still minimal, and application performance is not optimal. The purpose of this research is to find out how Electronic Government is implemented through the application of the Kelan Mobile Village Credit Institution at the Kelan Traditional Village Credit Institution, Badung Regency. Through the theory of e-government success elements according to Indrajit. The result in this study are that the application of the Kelan Mobile Village Credit Instituton at the Kelan Traditional Village Credit Institution has achieved good results on capacity and valueindicators. However, it is still not optimal, namely the support indicator. It is necessary to maximize socialization, conduct application usage assessment surveys, carry out application development, synergize with related parties, and the need for traditional villages to be involved in optimizing theKelan Mobile Village Credit Institution application. Keywords: Electronic Government, Kelan Traditional Village Credit Institution, Mobile Kelan Village Credit Institution Application